2012
DOI: 10.1258/ijsa.2012.012076
|View full text |Cite
|
Sign up to set email alerts
|

Local and systemic adverse effects of imiquimod therapy for external anogenital warts in men: report of three cases

Abstract: Imiquimod is a topical immune response modifier used to treat anogenital warts. Although considered a safe drug, mild to moderate local and systemic side-effects may occasionally occur. We report three cases of local and systemic adverse effects related to imiquimod, including one case that mimicked meningitis, which promptly resolved with drug cessation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 7 publications
0
10
0
2
Order By: Relevance
“…Therefore, TNF-α expression in SCC and BCC cell lines was determined and concentration-dependent response was plotted for the IMQ, IMQ-FO, and omega-3 fatty acids. Imiquimod is known for its inflammatory side effects 3,4 , and during the study IMQ concentrations appeared to increase the TNF-α expression in both carcinoma cell lines Fig. 5 .…”
Section: Tumor Necrosis Factormentioning
confidence: 87%
See 1 more Smart Citation
“…Therefore, TNF-α expression in SCC and BCC cell lines was determined and concentration-dependent response was plotted for the IMQ, IMQ-FO, and omega-3 fatty acids. Imiquimod is known for its inflammatory side effects 3,4 , and during the study IMQ concentrations appeared to increase the TNF-α expression in both carcinoma cell lines Fig. 5 .…”
Section: Tumor Necrosis Factormentioning
confidence: 87%
“…Imiquimod is an immune response modifier 1 and has been widely prescribed by dermatologists as a topical treatment, especially for curing skin conditions such as actinic keratosis, skin warts, and carcinoma 2 . Conversely, it is also known for its inflammatory-like side effects, such as severe skin inflammation 3,4 . In our earlier work, we demonstrated an interaction between fish oil and imiquimod 5 to explain observations seen in the delivery of imiquimod from fish oil-based gel system.…”
Section: Introductionmentioning
confidence: 99%
“…In randomized trials, the most common side effect of imiquimod is local erythema, which has been reported in up to 42% of patients [35] . Otherwise, it is well tolerated but occasionally can lead to more pronounced unwanted effects such as adenopathy [36] , severe eczema [37] , vitiligo [38] or meningitis [39] . In women with EPDV, imiquimod was generally well tolerated with mild-to-moderate local reactions in a majority of cases.…”
Section: Discussionmentioning
confidence: 99%
“…These inflammatory effects typically subside within 2 weeks of treatment discontinuation. Rare side effects include: psoriasiform eruptions and oral ulcers [11], and a meningitis-like effect that resolved upon cessation of treatment [12]. Also, because imiquimod is expensive, it may not be a feasible option for patients with certain insurance plans.…”
Section: Imiquimodmentioning
confidence: 99%